Acute glomerulonephritis secondary to Streptococcus anginosus. (9th March 2018) - Maharaj, Satish; Seegobin, Karan; Chrzanowski, Stephen; Chang, Simone
Abstract : Streptococcus anginosus is a clinically important pathogen that is emerging globally but remains poorly investigated. Here, we report the first case of acute glomerulonephritis resulting from infection with S. anginosus . Glomerulonephritis is typically caused by S. pyogenes and reports secondary to other strains including S. zooepidemicus and S. constellatus exist. Infection with S. anginosus in this patient was associated with acute nephritis (haematuria, oedema and hypertension), nephrotic syndrome and progressive azotemia. There was activation of the complement system. The presence of low C1q and elevated anti-C1q binding complexes points to a potential pathogenic role. Testing for streptococcal antigens was strongly positive. Emerging nephritogenic strains of S. anginosus present a significant health concern for both developed and developing countries.